The Tradition of Reading Surah Al-Rahman (Living Qur'an Study at Ma'had IDIA Putra Prenduan Sumenep) - Fauzi Fathur Rosi; Zainuddin (Penerbit Hellow Pustaka, 2024)
The Al-Qur'a n (living Qur'an) program in Ma'had IDIA became the master of Ma'hadi, which was maintained by the Master of IDIA son. Reading the Qur'a n by the Master of the program Plus TMI and Tahfidz is not correct in a certain letter, whereas in Ma'had IDIA son su>rah al-Rahma>n became the ruler of Ma'hadi. Implementation of the tradition of reading Su'rah al-Rahma'n in Ma'had IDIA son Prenduan is carried out every day after the prayer of the calf at exactly 11:30 WIB. The readings of Al-Rahma n are directed directly by Mu'allim, who is followed by the whole Mahasantri, and they begin by surrendering to the masjids before entering the readings of Al-Rahman, and by reciting the Su'rah al-Rahma with tartils together. The purpose and benefit of the tradition of reading Surah al-Rahma is to build a Mahasantri custom to read Su'rah al-Rahma after performing Dzuhur's prayer, enhance the work of Sha'lih and strive to thank God SWT. And hopefully God's SWT, gets the peace of mind as an emotional psychological cure for the Mahasantri.